Analisis Kinerja Keuangan pada PT. Perkebunan Nusantara (PTPN) X - Toni Adhitya (Department of Islamic Accounting, The Faculty of Islamic Economics and Business, State Islamic Institute of Kediri [IAIN Kediri, 2023)
According to the Minister of Finance of the Republic of Indonesia based on a decision on 28 June 1989, what is meant by financial performance is the achievements achieved by a company in a certain period which reflects the level of health of a company. This research aims to determine the financial performance of PT. Perkebunan Nusantara if calculated using the ratios contained in KEP-100/MBU-2002 and to determine financial performance if calculated using the standard weights of BUMN assessment indicators. This research uses a descriptive qualitative approach, namely research by processing data into something that is stated clearly and precisely. The results of this research show that the company PT. Perkebunan Nusantara experiencing unhealthy performance with the standard weight of the CCC assessment criteria indicators.